The risen Jesus - Bockmuehl, M (Cambridge University Press, 2024)
The resurrection of Jesus, pivotal to Christian history and praxis, is universally attested in early Christian sources, even if often critiqued or sidelined as myth or apologetics in modern scholarship. Paul’s letters and of the Gospels in their narrative diversity document the resurrection’s transformative and abiding impact on Jesus’s followers. In bringing the aspirations of myth and metaphor to fruition in time, the resurrection of Jesus is both an event in history and yet constitutes a new reality that transcends the register of available language and analogy.